IDENTIFIKASI RISIKO GANGUAN MUSKULOSKLETAL PADA PEKERJA PERCETAKAN DENGAN METODE NORDIC BODY MAP - moch sahri; Octavianus Hutapea; Rustam - Basuki (Dian Nuswantoro Semarang, 2021)
An increase in the amount of production in the printing industry will positively impact economic and social aspects. Economic and social aspects that can be directly felt include the increase in individual income and employment in the printing industry sector. Apart from having a positive impact, this also has a negative impact, especially on the health and protection aspects of workers related to occupational safety and health. The type of work in the printing industry is one that has a risk of musculoskeletal disorders. This study aims to determine the prevalence of complaints of musculoskeletal disorders among workers in the printing industry. The method used is a survey using a Nordic body map using a questionnaire. The results showed that 8% of workers experienced complaints on the musculoskeletal system. Complaints of disorders of the skeletal muscles experienced by workers complained of back pain (32%), complained of pain in the forearm and right shoulder (28%), complained of pain in the left shoulder, back and right upper arm (24%), complained pain in the neck, left upper and lower arm, right calf and left toe (20%).